Expression-dependent folding of interphase chromatin - Jerabek, Hansjörg; Heermann, Dieter W. (PLOS ONE, 2012)
Multiple studies suggest that chromatin looping might play a crucial role in organizing eukaryotic genomes. To investigate the interplay between the conformation of interphase chromatin and its transcriptional activity, we include information from gene expression profiles into a polymer model for chromatin that incorporates genomic loops. By relating loop formation to transcriptional activity, we are able to generate chromosome conformations whose structural and topological properties are consistent with experimental data. The model particularly allows to reproduce the conformational variations that are known to occur between highly and lowly expressed chromatin regions. As previously observed in experiments, lowly expressed regions of the simulated polymers are much more compact. Due to the changes in loop formation, the distributions of chromatin loops are also expression-dependent and exhibit a steeper decay in highly active regions. As a results of entropic interaction between differently looped parts of the chromosome, we observe topological alterations leading to a preferential positioning of highly transcribed loci closer to the surface of the chromosome territory. Considering the diffusional behavior of the chromatin fibre, the simulations furthermore show that the higher the expression level of specific parts of the chromatin fibre is, the more dynamic they are. The results exhibit that variations of loop formation along the chromatin fibre, and the entropic changes that come along with it, do not only influence the structural parameters on the local scale, but also effect the global chromosome conformation and topology.